2016
DOI: 10.1007/s10068-016-0218-0
|View full text |Cite
|
Sign up to set email alerts
|

Functional beverage from fermented soymilk with improved amino nitrogen, β-glucosidase activity and aglycone content using Bacillus subtilis starter

Abstract: The bioactivity of soymilk was enhanced by fermentation with three strains of β-glucosidaseproducing for 36 h at 37oC. The results indicated that protease, cellulase, and β-glucosidase activities were significantly (<0.05) increased with increasing fermentation time. In addition, the amino-type nitrogen content in -fermented soymilk was increased to 121.1-140.7 mg% after 36 h of fermentation. Among the isoflavones in soymilk, the contents of β-glucosides or acetyl-glucosides were decreased, while aglycone cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…rhamnosus D7 strain after 24 hr of fermentation. Hence, our results were obtained following other studies which support our findings (Baú & Ida, 2015; Champagne et al, 2010; Chun et al, 2008; Hati et al., 2017; Lee et al., 2016; Mendoza‐Avendaño et al., 2019; Rekha & Vijayalakshmi, 2010). Our study indicates that the selection of Lactobacillus strains depends upon the ability to deconjugation β‐glucosidic bonds.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…rhamnosus D7 strain after 24 hr of fermentation. Hence, our results were obtained following other studies which support our findings (Baú & Ida, 2015; Champagne et al, 2010; Chun et al, 2008; Hati et al., 2017; Lee et al., 2016; Mendoza‐Avendaño et al., 2019; Rekha & Vijayalakshmi, 2010). Our study indicates that the selection of Lactobacillus strains depends upon the ability to deconjugation β‐glucosidic bonds.…”
Section: Resultssupporting
confidence: 91%
“…Zhang and Yu (2019) studied that the production of isoflavone aglycones from soymilk by using LAB was increased up to 96.34% after 24 hr of fermentation. The production of SIA depends on different bacterial strains having the ability to produce β‐glucosidase (Lee et al., 2016; Otieno et al, 2006a). However, according to Yuksekdag et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that microorganisms use reducing sugars for their nutrition, decomposing them into alcohol and CO 2 to produce the components giving the unique flavors and tastes to fermented foods (Choi et al, 2018 ). Additionally, the amino-type nitrogen, which includes free amino acids formed by the action of proteases secreted by microorganisms during the fermentation of soybean products, is associated with the quality and flavor of gochujang (Lee et al, 2016 ; Kim et al, 2017 ). Amino-type nitrogen increased in soybean products after fermentation due to the continuous degradation of proteins by proteases.…”
Section: Discussionmentioning
confidence: 99%
“…Research by [28] which showed that the lactic acid bacteria which had the highest activity was B.subtillis HJ18-9.…”
Section: Resultsmentioning
confidence: 99%